2006
DOI: 10.1007/s00109-006-0079-8
|View full text |Cite
|
Sign up to set email alerts
|

HMG-CoA reductase inhibitors inhibit rat propylthiouracil-induced goiter by modulating the ras-MAPK pathway

Abstract: The aim of this study was to evaluate in vivo the antiproliferative effect of an inhibitor of isoprenoids metabolism, lovastatin, in an experimental model of propylthiouracil-induced goiter. In thyroid cells, thyrotropin (TSH)-induced proliferation requires active isoprenoid synthesis, and the HMG-CoA reductase inhibitors have antiproliferative effects in vitro. Propylthiouracil treatment (PTU) of rats led to thyroid hypertrophy and hyperplasia by TSH-induced activation of the mitogen-activated protein kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 38 publications
0
12
0
3
Order By: Relevance
“…PTU treatment is known to cause decreased T 3 production with subsequent increase in TSH, thyroid enlargement, and activated thyroid function (Levey 1963, al-Alawi et al 1995, Laezza et al 2006; we therefore treated four rats with PTU ad libitum and killed the animals after 2 weeks to isolate the thyroids. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PTU treatment is known to cause decreased T 3 production with subsequent increase in TSH, thyroid enlargement, and activated thyroid function (Levey 1963, al-Alawi et al 1995, Laezza et al 2006; we therefore treated four rats with PTU ad libitum and killed the animals after 2 weeks to isolate the thyroids. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In a 2006 study conducted on rats, Laezza et al [15] reported that HMG-CoA reductase inhibitors inhibited propylthiouracyl-induced goiter by p21 ras-MAPK pathway modulation. Even though different molecular and genetic processes have been proposed, results show that lovastatin is an effective inhibitor in goitrogenesis with p21 ras farnesylation inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Ras mutation activation and other oncogenes are common in thyroid tumors; ras mutations may also be present in nodular hyperplasia of the thyroid [13, 14]. In a 2006 study performed on rats, Laezza et al [15] showed that HMG-CoA reductase inhibitors inhibit propylthiouracil-induced goiter with p21 ras-MAPK (mitogen-activated protein kinase) pathway modulation. Thus, statins may offer a new treatment alternative for benign and malignant proliferative thyroid diseases.…”
Section: Introductionmentioning
confidence: 99%
“…After 3 days of acclimatization, the rats were randomly divided into 5 groups: normal, model, Euthyrox, HYDf, and HYDp groups; all rats except those in the normal control group received intragastric administration of PTU at a dosage of 0.01 g/kg daily for 14 days to induce the goitrous model according to previously reports [15] and were given different treatments for 28 days, as shown in Table 2.…”
Section: Methodsmentioning
confidence: 99%